# How do you solve #x / 30 - 1/(5x) = 1/6#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation x / 30 - 1/(5x) = 1/6, we can start by finding a common denominator for the fractions. The common denominator is 30x. Multiplying each term by 30x, we get:

x * (30x / 30) - (1/(5x)) * (30x / 30) = (1/6) * (30x / 30)

This simplifies to:

x^2 - 6 = 5x

Rearranging the equation:

x^2 - 5x - 6 = 0

Factoring the quadratic equation:

(x - 6)(x + 1) = 0

Setting each factor equal to zero:

x - 6 = 0 or x + 1 = 0

Solving for x:

x = 6 or x = -1

Therefore, the solutions to the equation are x = 6 and x = -1.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you simplify #(2a^2-a-6 )/(2a^2+7a+6)*(a^2-2a-8)/(a^2+a-6)#?
- How do you simplify # (bc)/(pi*a) + (ac)/(pi*b) + (ab)/(pi*c)#?
- How do you solve #\frac { 3v - 7} { 2} + \frac { v - 9} { 4} = 10?#
- How do you simplify #(x^2+12x+20)/(4x^2-9)*(6x^3-9x^2)/(x^3+10x^2)*(2x+3)#?
- How do you solve for x ? #(x-2)(x-3)=34/33^2#

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7